Kemampuan Komunikasi Matematis Siswa dalam Memecahkan Masalah Pada Materi Peluang Ditinjau dari Gaya Belajar - Az Zahra, Destrilia Fitri; Rahaju, Endah Budi (MATHEdunesa, 2025)
This purpose of this study is to describe students' written and oral mathematics communication abilities in solving probability problems based on their learning styles. This research uses a qualitative approach with qualitative description research methods. The subjects of this study were three ninth grade junior high school students with different learning styles (visual, auditory, and kinesthetic), equivalent mathematical ability, and the same gender. Data were collected from learning style questionnaires, mathematics ability tests, mathematical communication ability tests (both written and oral), and interviews. The mathematical communication ability test was analyzed using the mathematical communication ability indicators from Nurhasanah et al. (2019). The results of the study showed that in written mathematical communication, students with visual, auditory, and kinesthetic learning styles met four indicators: expressing a problem in mathematical ideas, expressing a problem in mathematical models, solving problems in an organized and structured way, and evaluating mathematical ideas. The difference is that visual students do not write what is asked but explain it through interviews, auditory students do not make a problem-solving plan, and there are inaccuracies in problem-solving among visual and kinesthetic students. In oral mathematical communication, students with visual, auditory, and kinesthetic learning styles met four indicators: expressing a problem in mathematical ideas, expressing a problem in mathematical models, solving problems in an organized and structured way, and evaluating mathematical ideas. The difference is that auditory students do not explain the information that is asked directly but rather through interviews. The benefits of this study can be used as a basis for designing teaching strategies that can improve students' mathematical communication abilities and to further develop future research.